2020
DOI: 10.1108/ics-02-2019-0029
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of AI-integrated CRM system by Indian industry: from security and privacy perspective

Abstract: Purpose The purpose of this study is to make an attempt to identify the factors responsible for the adoption of an artificial intelligence (AI)-integrated customer relationship management (CRM) system in Indian organizations with a special focus on security and privacy issues. Design/methodology/approach This study was conducted for the identification of factors responsible for the adoption of the AI-integrated CRM system in Indian organizations focusing attention on security and privacy perspective. For thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

6
4

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 85 publications
(65 reference statements)
0
30
0
1
Order By: Relevance
“…Juang and Jing revealed that various technologies, especially digital payment should have the security that is adequate (Jung & Jang, 2014). According to research earlier, perceived security proved to be one of the factors that is important in improving trust (Khalilzadeh et al, 2017;Mostafa, 2020;Roca et al, 2009) and behaviour intention (Alshurideh et al, 2021;Chatterjee et al, 2020;Mostafa, 2020;Semerikova, 2020). So based on these explanations, several hypotheses that can be proposed in this study are: H4 = Perceived Security has a significant positive effect on Trust of Digital Payment using QR Code H5 = Perceived Security has a significant positive effect on Behavior Intention of Digital Payment using QR code.…”
Section: Perceived Securitymentioning
confidence: 78%
“…Juang and Jing revealed that various technologies, especially digital payment should have the security that is adequate (Jung & Jang, 2014). According to research earlier, perceived security proved to be one of the factors that is important in improving trust (Khalilzadeh et al, 2017;Mostafa, 2020;Roca et al, 2009) and behaviour intention (Alshurideh et al, 2021;Chatterjee et al, 2020;Mostafa, 2020;Semerikova, 2020). So based on these explanations, several hypotheses that can be proposed in this study are: H4 = Perceived Security has a significant positive effect on Trust of Digital Payment using QR Code H5 = Perceived Security has a significant positive effect on Behavior Intention of Digital Payment using QR code.…”
Section: Perceived Securitymentioning
confidence: 78%
“…The concept of value cocreation is associated with metacontextual activities that mainly depend on the characteristics of the consumers' lifestyle (Busser and Shulga, 2019). Marketing concepts include value-in-exchange (depends during sale time) (Ruiz-Alba et al, 2019) and value-in-use (after-sale issues) (Erhardt et al, 2019;Ghosh et al, 2020b). The co-creation value depends more on the valuein-use concept that includes dissemination of the use-experience of the consumers (Alzaydi et al, 2018;Roy et al, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The CRM tool helps an organization to know the customers more systematically and methodically "by identifying a company's best customers and maximizing the value from them by satisfying and retaining them" (Kennedy, 2006, p. 58). The AI integrated CRM system is essential for improving the analysis system of a huge volume of data of customers facing less complexity (Wen and Chen, 2010;Nguyen and Simkin, 2013;Chatterjee et al, 2020c). However, such adoption of AI integrated CRM system in the organizations will be deemed to be successful if the users (employees) realize its utility and appreciate the use by feeling pleasure and enjoyment to use this complex but effective system (Nguyen and Mutum, 2012;Roy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%